Peran perpustakaan sekolah dalam meningkatkan minat literasi siswa di SD Muhammadiyah Plus Kota Salatiga - Silfana Wiwit Soliha (Nur Science Institute, 2026)
The school library serves as a pivotal educational pillar, offering dynamic learning spaces and comprehensive resources to foster students' literacy. This study investigates the role of the library at SD Muhammadiyah Plus Kota Salatiga in enhancing students’ literacy interest through innovative programs like